2021
DOI: 10.1101/2021.05.08.21256890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do people with low back pain walk differently? A systematic review and meta-analysis

Abstract: Objective To identify differences in biomechanics during gait in individuals with acute and persistent low back pain compared with back-healthy controls. Design Systematic review Data Sources A search was conducted in PubMed, CINAHL, SPORTDiscus, and PsycINFO in June 2019 and was repeated in December 2020. Eligibility criteria Studies were included if they reported biomechanical characteristics of individuals with and without low back pain during steady-state or perturbed walking and running. Biomechanical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 137 publications
(240 reference statements)
0
5
0
Order By: Relevance
“…In recent years, increasing attention was given toward the role of paraspinal muscle in pathogenesis of spinal disorders. Multiple studies have showed correlation between PSM degeneration with back pain, radiculopathy, and spinal deformity (19,21,(26)(27)(28). Similarly, Lee et al reported extensive degeneration of back muscle could be a causative factor in the pathogenesis of flat back syndrome (23).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent years, increasing attention was given toward the role of paraspinal muscle in pathogenesis of spinal disorders. Multiple studies have showed correlation between PSM degeneration with back pain, radiculopathy, and spinal deformity (19,21,(26)(27)(28). Similarly, Lee et al reported extensive degeneration of back muscle could be a causative factor in the pathogenesis of flat back syndrome (23).…”
Section: Discussionmentioning
confidence: 98%
“…The quality and quantity of paraspinal muscle were reported to be correlated with age and gender (20,21). To eliminate those confounding factors, this retrospective cohort study included female patients with DS that attended our hospital during the period from February 2017 to December 2020.…”
Section: Patient Selectionmentioning
confidence: 99%
“…CNLBP is a highly prevalent global public health issue ( Van et al, 2006), causing not only physical and psychological harm to patients but also incurring signi cant nancial costs that must be addressed [75]. Exercise treatment has been demonstrated to alleviate symptoms in individuals with CNLBP, according to several studies [76, 77,78].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of gait changes, patients with LBP demonstrated reduced gait speed and shorter stride length compared to painfree controls (Smith et al, 2022). To initiate walking, body weight should be voluntarily shifted to one side to facilitate the stride on the other.…”
Section: Introductionmentioning
confidence: 99%
“…When the ipsilateral side of the lower limb transitions from the support phase to the swing phase, effective weight shifting to the contralateral side can be beneficial for enhancing the gait cycle (Alcock et al, 2013). A systematic review showed that it may be challenging for patients with LBP to maintain normal gait and stable posture consecutively, possibly due to impaired control of lateral weight shifting (Smith et al, 2022).…”
Section: Introductionmentioning
confidence: 99%